Evaluation scores processing and interpretation techniques - Nurhasanah, Siti; Arbeni, Wawan; Meysella, Nofi; Elyza, Nova; Tarigan, Sri Rehna Ramadhani Br (EDUCTUM: Journal Research, 2026)
The processing and interpretation of evaluation scores is a crucial step in learning assessment because it determines the validity of information regarding student learning outcomes. Technological developments have driven significant changes in evaluation data processing techniques, from manual approaches to the use of digital technology. This article aims to examine manual and digital evaluation score processing techniques and to analyze the process of interpreting evaluation results systematically and meaningfully. The method used is a literature study with a qualitative descriptive approach through a review of various textbooks, journal articles, and scientific documents relevant to educational evaluation and the use of assessment technology. The results of the study indicate that digital-based evaluation data processing has advantages in terms of efficiency, accuracy, and ease of analysis compared to manual techniques, although the manual approach is still relevant under certain conditions. Appropriate analysis and interpretation of evaluation results can help educators understand the level of learning achievement, identify remedial or enrichment needs, and support objective learning decision-making. Thus, mastery of evaluation score processing and interpretation techniques is an important competency for educators in improving the quality of assessment and the learning process.